Gami–Chunggan Formula Prevents Motor Dysfunction in MPTP/p-Induced and A53T α-Synuclein Overexpressed Parkinson’s Disease Mouse Model Though DJ-1 and BDNF Expression - Ahn, Sora; Liu, Quan Feng; Jang, Jae-Hwan; Park, Jeonghun; Jeong, Ha Jin; Kim, Youngman; Kim, Dong-hee; Jeong, Guwon; Oh, Seung Tack; Park, Seong-Uk; Cho, Seung-Yeon; Park, Hi-Joon; et al. (Frontiers in Aging Neuroscience, 2019)
The Gami-Chunggan formula (GCF) is a modification of the Chunggan (CG) decoction, which has been used to treat movement disorders such as Parkinson’s disease (PD) in Traditional East Asian Medicine. To evaluate the neuroprotective effects of GCF in chronic PD animal models, we used either a 5-week treatment of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine with probenecid (MPTP/p) or the α-synuclein A53T overexpressed PD mouse model. C57BL/6 mice were treated with MPTP, in combination with probenecid, for 5 weeks. GCF was administered simultaneously with MPTP injection for 38 days. The A53T α-synuclein overexpressed mice were also fed with GCF for 60 days. Using behavioral readouts and western blot analyses, it was observed that GCF prevents motor dysfunction in the MPTP/p-induced and A53T α-synuclein overexpressed mice. Moreover, GCF inhibited the reduction of dopaminergic neurons in the substantia nigra (SN) and fibers in the striatum (ST) against MPTP/p challenge. The expression of DJ-1 was increased but that of α-synuclein was decreased in the SN of PD-like brains by GCF administration. In vitro experiments also showed that GCF inhibited 6-OHDA-induced neurotoxicity in SH-SY5Y neuroblastoma cell lines and that it did so to a greater degree than CG. Furthermore, GCF induced BDNF expression through phosphorylation of Akt, ERK, CREB, and AMPK in the SN of PD-like brains. Therefore, use of the herbal medicine GCF offers a potential remedy for neurodegenerative disorders, including Parkinson’s disease.